Downward wage rigidity in Hungary - Gábor Kátay (European Central Bank (ECB), 2011)
Following the approach recently developed for the International Wage Flexibility Project (IWFP), the paper presents new estimates of downward real and nominal wage rigidity for Hungary. Results suggest that nominal rigidity is more prominent in Hungary than real rigidity. When compared to other countries participating in the IWFP, Hungary ranks among the countries with the lowest degree of downward real rigidity. The estimated downward nominal rigidity for Hungary is higher, the measure is close to but still below the overall cross-country average. Using the same methodology, the paper also confirms the widespread view that the wage growth bargained at the national level has little compulsory power in Hungary. On the other hand, the minimum wage remains an important source of potential downward wage rigidity in Hungary.
Keywords: C23; E24; J3; J5; 330; Downward nominal and real wage rigidity; Wage change distributions; wage flexibility; Lohnrigidität; Reallohn; Mindestlohn; Schätzung; Ungarn